Pan‑cancer analysis of the oncogenic role of telomeric repeat binding factor 2 (TERF2) in human tumors and in vitro validation in gastric cancer by TERF2 knockdown - Qiang Ma; Wen Xu; Xiaolan Guo (Discover Oncology)
Abstract Background Telomeric repeat binding factor 2 (TERF2), a key component of the Shelterin complex, is crucial for maintaining telomere integrity and genome stability. While the involvement of TERF2 in tumorigenesis and progression has been documented, comprehensive pan-cancer analyses of TERF2 across different malignancies remain scarce. Methods In the present study, the expression, mutations, immune cell infiltration, and interacting genes of TERF2 were systematically evaluated through bioinformatics analysis, and in vitro experiments were performed to elucidate the functional roles of TERF2 in gastric cancer. Results The findings revealed that TERF2 was predominantly upregulated in cholangiocarcinoma (CHOL), diffuse large B-cell lymphoma (DLBC), pancreatic adenocarcinoma (PAAD), stomach adenocarcinoma (STAD), and thymoma (THYM), correlating with tumor progression. Amplification and mutations were identified as the primary alterations of TERF2, particularly associated with liver hepatocellular carcinoma (LIHC). Furthermore, TERF2 expression was linked to the infiltration of cancer-associated fibroblasts and immune cells in certain cancer types. Protein–protein interaction (PPI) analysis highlighted several genes associated with TERF2, including CTCF, DDX19A, MATR3, ZFP1, and ZFP90. Additionally, in vitro experiments demonstrated that TERF2 knockdown significantly suppressed the proliferation and migration of gastric cancer cells. Conclusions These results suggest that dysregulation and mutations of TERF2 are prevalent across various cancers, contributing to tumor immunity and acting as an oncogenic factor, thus positioning TERF2 as a potential therapeutic target in cancer treatment.